General Holmstedt’s Formulae for the K-Functional - Irshaad Ahmed; Georgi E. Karadzhov; Ali Raza (Journal of Function Spaces)
Explicit formulae for the K-functional for the general couple ((A0,A1)Φ0,(A0,A1)Φ1), where (A0,A1) is a compatible couple of quasi-normed spaces, are proved. As a consequence, the corresponding reiteration theorems are derived.